Exploring Digital Source of Information on Opportunity Recognition for Future Entrepreneurs: Self-Efficacy as the Mediator - Herlina, Maria Grace; Ozgen, Eren; Handranata, Yunita Wijaya; Rinaldi, Banu (Journal of Education Culture and Society, 2025)
Aim. This article examines how digital platforms, applications, and artifacts affect opportunity recognition in entrepreneurship education, focusing on self-efficacy among Indonesian undergraduates. The aim is to understand how these digital resources help students recognise entrepreneurial opportunities and develop entrepreneurial competencies. Methods. A cross-sectional survey of 202 undergraduates in Greater Jakarta, Indonesia, assessed their use of digital platforms, applications, and artifacts. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the relationships among digital sources, self-efficacy, and opportunity recognition. Results. The study finds that digital platforms and applications help students identify entrepreneurial opportunities, with self-efficacy partially mediating the effects of digital artifacts. Digital artifacts increased self-efficacy but did not directly influence opportunity recognition. The findings emphasise the need for interactive digital tools in entrepreneurship education and highlight the critical role of self-efficacy in the learning process. Conclusion. Digital platforms and applications significantly contribute to students’ opportunity recognition, while digital artifacts support the development of self-efficacy. Enhancing self-efficacy is essential for optimising digital learning outcomes in entrepreneurship education. Research restrictions. The study is limited to undergraduate students in Greater Jakarta, which may limit the generalisability of the findings. Future research should explore broader demographic and cross-cultural contexts.